2019
DOI: 10.1101/719229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative Cellular-Resolution Map of the Oxytocin Receptor in Postnatally Developing Mouse Brains

Abstract: AbstractOxytocin receptor (OTR) plays critical roles in social behavior development. Despite its significance, brain-wide quantitative understanding of OTR expression remains limited in postnatally developing brains. Here, we validated and utilized fluorescent reporter mice (OTRvenus/+) to examine OTR cells across postnatal periods. We developed postnatal 3D template brains to register whole brain images with cellular resolution to systematically quantify O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 65 publications
(99 reference statements)
0
35
0
Order By: Relevance
“…Previous studies suggested a mismatch between presynaptic OT projection and postsynaptic OTR expression (3,34), yet quantitative brain-wide comparison has not been conducted. Previously, we validated that OTR-Venus mice represent the endogenous OTR expression faithfully (11). We imaged a cohort of adult OTR-Venus mice using serial twophoton tomography and mapped OTR expression in the whole adult brain (n=14, green in Table S3. 4A).…”
Section: Comparison Of Oxytocin Output and Oxytocin Receptor Expressionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies suggested a mismatch between presynaptic OT projection and postsynaptic OTR expression (3,34), yet quantitative brain-wide comparison has not been conducted. Previously, we validated that OTR-Venus mice represent the endogenous OTR expression faithfully (11). We imaged a cohort of adult OTR-Venus mice using serial twophoton tomography and mapped OTR expression in the whole adult brain (n=14, green in Table S3. 4A).…”
Section: Comparison Of Oxytocin Output and Oxytocin Receptor Expressionmentioning
confidence: 98%
“…The rest of the OT neurons are expressed in 10 different brain regions (Table S1). The Cre-driven reporter system used in the present study permanently labels all Cre positive cells including developmentally transient expression (11). To distinguish neurons actively expressing OT in adult from developmentally labeled cells, we performed immunohistochemistry using an OT antibody in OT:Ai14 mice.…”
Section: Quantitative Expression Of Oxytocin Neurons In the Mouse Brainmentioning
confidence: 99%
“…Serial two photon tomography (STPT) imaging. Prior to imaging, the brain sample was embedded in oxidized agarose and cross-linked in 0.05M sodium borohydrate at 4C for at least 2 days ahead of imaging (Kim et al, 2017;Newmaster et al, 2019). This procedure allows for seamless cutting at 50μm thick sections, while also preventing any tearing of the brain surface.…”
Section: Animalsmentioning
confidence: 99%
“…Signals in the green and red spectrum were simultaneously collected using a 560 nm dichroic mirror (Chroma). For pericyte and neuronal subtypes, STPT imaging was conducted with 1x1 μm (x,y) resolution in every 50 μm (z), with the imaging plane set at 40μm deep from the surface, as previously described (Kim et al, 2017;Newmaster et al, 2019). For vascular imaging, optical imaging (5 μm z step, 10 steps to cover 50μm in z) was added in the imaging, producing 1x1x5 μm (x,y,z) resolution beginning at 20μm deep from the surface.…”
Section: Animalsmentioning
confidence: 99%
“…These brains were stored in 0.05M phosphate buffer (PB) at 4°C until imaging. Detailed information about STPT imaging and analysis were previously described (Jeong et al, 2016;Newmaster et al, 2020). Briefly, the brain samples were embedded in oxidized 4% agarose and cross-linked by 0.05M sodium borohydride for imaging preparation.…”
Section: Stpt Imaging and Data Analysismentioning
confidence: 99%